Diuretic Effectiveness Test of Leucare Leucabeth (Leucaena leucocephala (Lam.) de Wit) Ethanol Extract on Male White Rats (Rattus norvegicus) - Muhammad Gunawan; Tanjung, Siti Aisyah; Fitriani, Enny (International Journal of Public Health Excellence (IJPHE), 2025)
Leucaena leucaena seeds are widely believed to be a plant that can treat various ailments, including diuretics. Leucaena seeds contain a high amount of alkaloids, saponins, flavonoids, tannins, protein, fat, calcium, phosphorus, iron, amino acids, and leucanol. The purpose of this study was to determine whether ethanol extract of leucaena seeds can have a diuretic effect on male white rats. This study used 30 male white rats divided into five groups: Group I (solvent control) with 1% CMC. Group II (comparison) with furosemide. Groups III, IV, and V (treatment) were given ethanol extract of leucaena seeds at doses of 150 mg/kg BW, 300 mg/kg BW, and 600 mg/kg BW, respectively. The test preparations were administered orally using a metabolic cage equipped with a rat urine collector. Observations were made every hour for 8 hours to determine total urine volume. The urine volume of each group was statistically analyzed using ANOVA and the LSD test. The results of the statistical test of urine volume between the furosemide and ethanol extract groups of lamtoro seeds (Leucaena leucocephala (Lam.) de Wit) showed no significant difference. From the results of the study, it can be concluded that the higher the concentration of EEBL suspension given, the more urine volume will be produced, and when the EEBL suspension was given at a dose of 600 mg/kg BW, the results were almost comparable to the group of animals given furosemide suspension.